TEPAK CIWARINGINAN PADA SENI PENCAK SILAT DI KOTA BANDUNG - Oktriyadi, Riky; Sentosa, Gempur (LP2M ISBI Bandung, 2023)
Pencak silat is a martial art of Indonesia's cultural identity that has been designated by UNESCO as an Intangible Cultural Heritage. Pencak silat in West Java is not only categorized as a martial sport, but also as one of the arts. Pencak silat in the context of performing arts is often called Kendang Penca (from the perspective of musical aesthetics) and Ibing Penca (from the perspective of dance aesthetics). The focus of this article is to describe the variety of tepak ciwaringinan patterns in the pencak silat family in Bandung. The consideration is that these songs and tepak no longer appear in every kendang penca performance, it can be said that their existence is starting to become extinct. In this article, the author uses a qualitative approach from Jhon W. Creswell by collecting data through observation, documentation, and interviews. After the data is obtained, the author then analyzes the data to test the truth of the data. This article discusses an overview of pencak silat as a performing art, the musical accompaniment of pencak silat in Bandung, and a description of the Ciwaringinan tepak pattern in pencak silat. The article concludes that pencak silat is one of the most important aspects of the performing arts in Indonesia, especially in West Java. Aesthetically, pencak silat generally consists of the aesthetics of the Pencak Silat dance form (ibing penca), music aesthetics (karawitan), and traditional fashion aesthetics. In addition, the findings in this study are that there are a variety of Ciwaringinan tepak patterns that have not been recognized by the public.